2019
DOI: 10.2106/jbjs.18.00642
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Radiographic Osteoarthritis Severity Modifies the Effect of Preoperative Pain on Pain/Function After Total Knee Arthroplasty

Abstract: Background: Osteoarthritis (OA) severity as demonstrated by preoperative radiographs and preoperative pain play an important role in the indication for total knee arthroplasty (TKA). We investigated whether preoperative radiographic evidence of OA severity modified the effect of preoperative self-reported pain on postoperative pain and function 1 and 2 years after TKA for OA. Methods: Data from the Longitudinal Leiden Orthopaedics Outcomes of Osteoarthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 47 publications
4
46
0
Order By: Relevance
“…Finally, in our subgroup analyses, the patient numbers were rather small, especially for men, which hampered conclusiveness. However, despite the smaller patient number, our results were in line with previous findings [32].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Finally, in our subgroup analyses, the patient numbers were rather small, especially for men, which hampered conclusiveness. However, despite the smaller patient number, our results were in line with previous findings [32].…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, we observed less improvement postoperatively in patients having at least one comorbidity compared with patients without comorbidities. Furthermore, we observed greater improvements in patients with preoperatively more severe radiographic OA compared with patient with no to minimal radiographic OA, which is in line with previous findings in the LOAS study [32,33], and with others [34,35]. However, not all previous studies are in agreement [36,37], which could be explained by the inclusion of a limited patient number [36], including only patients with mild radiographic OA in contrast to also including patients with no radiographic OA [36,37], as well as other differences in patient characteristics such as higher age.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, there are issues inherent with diagnosis of OA with radiographs which confounds clinical practice. It is therefore timely and apt that van de Water et al (5) conducted a multicentre prospective cohort study of 599 patients, evaluating the effects of preoperative radiographic OA severity on preoperative pain. Their article is entitled, "Preoperative Radiographic Osteoarthritis Severity Modifies the Effect of Preoperative Pain on Pain/Function After Total Knee Arthroplasty: Results at 1 and 2 Years Postoperatively".…”
mentioning
confidence: 99%
“…The authors reported that patients with milder radiographic OA were likely to be operated on as a result of their pain rather than radiographic OA severity, as confirmed by similar baseline pain levels across all four different Kellgren-Lawrence groups. Sources of pain that may not be evident on radiographs include extra-articular pathologies, psychosomatic conditions (6) or central pain sensitization (5). Patients with higher pain scores and lower Kellgren-Lawrence grades demonstrated more central pain sensitization (7), which subsequently lead to less improvement following TKA compared with patients with high Kellgren-Lawrence grades and high pain levels (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation